Synthesis of Pyrazole Dyes Derivatives - Gheath, Abdalla; Elsharif, Nada; Alabiedy, Entesar (Libyan Journal of Science &Technology, 2022)
Eight azo dyes were prepared by diazotization of 5-amino-3 (cyanomethyl)-1H- pyrazole-4-carbonitrile in presence of sodium nitrite and hydrochloric acid at 0°C. We reported that the malononitrile molecule was a very active nucleophile, where can react with the diazonium salt of pyrazole in presence of sodium acetate and ethanol to yield corresponding azo dyes of pyrazole. The dyes were characterized by elemental analysis and spectral methods. In addition, the effect of the pH value on the products yield of the dyes was reported.